Tourists' perceptions of beach quality improvement during the off-peak season: a segmentation approach - Lukoseviciute, Goda (2021)
Recently coastal tourism has increased dashingly, however, it has negatively affected environmental, social and cultural sustainability. Algarve is the most touristic place in Portugal with a large number of beautiful beaches. Due to negative tourism impacts and climate change, coastal tourism management tools need to be assessed and implemented. Most beach areas have the dual mandate of conserving natural resources as well as providing opportunities for recreation and tourism. This paper aims identify off-peak season beach user profiles and segment them according to their priorities for sustainable beach management in the face of climate change and seasonality balance. An urban, rural, resort and remote beach types were chosen at Albufeira municipality as case studies. A cluster analysis was applied to survey data collected through 200 face-to-face interviews. The survey aimed to get beach visitor’s opinion of beach environment, services and quality attributes´ importance. Cluster analyses have resulted in four beach user profiles: passive nature-lovers, senior consumerists, outliers and young and active environmentalists. The results provide valuable information and insights both for academics and for beach managers, who can adjust management according to the clustered markets and their preferences.